The Effect Of Gender Diversity And The Effectiveness Of Audit Committees On Audit Report Lag: Empirical Evidence From Manufacturing Companies In Indonesia - Tanggor Sihombing; Taufiq Hidayat (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2025)
This study tests the hypothesis regarding the influence of four variables on audit report lag (ARL) as the dependent variable. The four independent variables are gender diversity, the expertise of the audit committee chair, the number of audit committee members, and the frequency of audit committee meetings. The researcher employed purposive sampling to select the study population. The observed population consists of publicly listed manufacturing companies. After the sampling process, the final sample comprised 465 data points representing three fiscal years from 2021 to 2023. Audit report lag is calculated as the number of days from the beginning of the fiscal year to the date of the audit report. The results show that gender diversity and the number of audit committee members, particularly in Indonesian companies, do not affect audit report lag. Meanwhile, the frequency of audit committee meetings and the expertise of the audit committee chair—measured by accounting or auditing background—can reduce the audit report lag.